2006
DOI: 10.1002/adem.200600049
|View full text |Cite
|
Sign up to set email alerts
|

High Speed PVD Thermal Barrier Coatings

Abstract: in coating cross sections. Transmission electron microspy (TEM) was carried out by using Tecnai F20 microscope equiped with Gatan UltraScan camera.Magnetization curves of the sprayed coatings were measured by a custombuilt vibrating sample magnetometer (VSM). Measurements were made both with the magnetic field in plane and perpendicularly to the plane. For calibration pure Ni sample was used.Wet corrosion tests were carried out in order to study the density of the coatings and location of the nickel particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The high‐speed physical vapor deposition (HS‐PVD) is a special variant of the PVD process and belongs to the family of sputter techniques, which is based on hollow cathode discharge (HCD) and gas flow sputtering (GFS). [ 16 ] In a reactive HS‐PVD process, the metallic target is first atomized and convectively removed from the sputter source via the inert gas flow. [ 17 ] The reactive gas is added outside the hollow cathode and so has less contact to the target surface.…”
Section: Introductionmentioning
confidence: 99%
“…The high‐speed physical vapor deposition (HS‐PVD) is a special variant of the PVD process and belongs to the family of sputter techniques, which is based on hollow cathode discharge (HCD) and gas flow sputtering (GFS). [ 16 ] In a reactive HS‐PVD process, the metallic target is first atomized and convectively removed from the sputter source via the inert gas flow. [ 17 ] The reactive gas is added outside the hollow cathode and so has less contact to the target surface.…”
Section: Introductionmentioning
confidence: 99%
“…The high speed physical vapor deposition (HS‐PVD) is a special variant of the PVD process and belongs to the family of sputter techniques which is based on hollow cathode discharge (HCD) and gas flow sputtering (GFS). [ 30 ] Due to the unique gas flow‐driven material transport, line‐of‐sight characteristic of conventional PVD technologies is overcome by means of HS‐PVD technology. Moreover, previous studies have shown that (Ti,Al,Si)N coatings, deposited by HS‐PVD, had a promising potential for the erosion protection of compressor blades, due to their dense microstructures, smooth surfaces, and a high bonding strength between coating and substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the unique combination of the highly ionized plasma and the gas flow-driven material transport, high-rate deposition of physical vapor deposition coatings with a dense microstructure and a high bonding strength can be achieved [33,34].…”
Section: Introductionmentioning
confidence: 99%